2006
DOI: 10.1158/1078-0432.ccr-06-0861
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducers and Activators of Transcription 3 Pathway Activation in Drug-Resistant Ovarian Cancer

Abstract: Purpose: One of the major obstacles in the treatment of ovarian cancer is the development of multidrug resistance. Recent evidence shows that high-grade ovarian cancer often shows activation of the signal transducers and activators of transcription 3 (Stat3) pathway with subsequent transcription of genes that support tumor growth and survival. Less studied is the role of the Stat3 pathway in acquired drug resistance. There is no information on Stat3 expression in chemotherapy naI« ve ovarian cancer as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
230
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 39 publications
9
230
0
1
Order By: Relevance
“…Previously, we have found that IL-6 is secreted in high levels by several paclitaxel-resistant ovarian cancer cell lines, including SKOV-3 TR and OVCAR8 TR [7,8]. SKOV-3 TR and OVCAR8 TR cells were plated at 1×10 5 cells per well in 24-well plates and treated with CDDOMe in both a time-and dose-dependent manner.…”
Section: Il-6 Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have found that IL-6 is secreted in high levels by several paclitaxel-resistant ovarian cancer cell lines, including SKOV-3 TR and OVCAR8 TR [7,8]. SKOV-3 TR and OVCAR8 TR cells were plated at 1×10 5 cells per well in 24-well plates and treated with CDDOMe in both a time-and dose-dependent manner.…”
Section: Il-6 Measurementsmentioning
confidence: 99%
“…SKOV-3 TR and OVCAR8 TR cells were plated at 1×10 5 cells per well in 24-well plates and treated with CDDOMe in both a time-and dose-dependent manner. The supernatants were collected at different time points and kept at −20° C. IL-6 levels in culture supernatants were measured using a quantitative ELISA kit (R&D Systems, Minneapolis, MN) as described previously [7,8]. The absorbance of each well was read using a BT 2000 Microkinetics Reader (Bio-Tek Instrument Inc. Winooski, VT) at 450 nm.…”
Section: Il-6 Measurementsmentioning
confidence: 99%
See 3 more Smart Citations